Unraveling the thermodynamic criteria for size-dependent spontaneous phase separation in soft porous crystals - Sven M. J. Rogge (Nature Portfolio, 2019)
Soft porous crystals hold big promise as functional nanoporous materials due to their stimuli responsive flexibility. Here, molecular dynamics simulations reveal a new type of spatial disorder in mesoscale crystals that helps to understand the size-dependency of their phase transition behavior.